Analisis Kewenangan Bawaslu dalam Pengawasan Pemilu: Perspektif Hukum Siyasah - Syamsul Wathoni; Luluk Indarinul Mufidah (Universitas Pangeran Diponegoro Nganjuk, 2024)
The Election Supervisory Body (Bawaslu) plays a strategic role in ensuring that Indonesia's democratic processes are conducted fairly, transparently, and free from violations. This study examines Bawaslu's authority through the lens of siyasah law, emphasizing justice, transparency, and accountability in public governance. It highlights prevention, enforcement, and dispute resolution as the core aspects of election supervision. From the siyasah syar’iyyah perspective, Bawaslu’s role embodies the execution of public trust to maintain political stability and social harmony. The study recommends strengthening regulations based on siyasah values and optimizing political education to enhance public participation in election supervision.